O que fazem - ou deveriam fazer - os governos estaduais na gest\~ao das políticas sociais - Elaine Cristina Licio; Pedro Lucas de Moura Palotti; Aérica de Figueiredo Pereira Meneses; Pedro Arthur de Miranda Marques Pontes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– With a time frame that covers the period after the Federal Constitution of 1988 promulgation, this text describes, analyzes and compares the main attributions reserved to the state governments in the field of education, health and social assistance policies. In addition, it addresses the way in which states have in fact acted on the three policies over this period. The states maintained relevant roles in the provision of services, took charge of co-financing and were asked to respond for technical support so that the municipalities could structure their own offer in basic services, although with significant variation in the way they have actually assumed them. For various reasons, even arising from legacy implementation and political priorities of each entity, it was observed that this variation is greater in aspects whose regulation is less effective, such as in social assistance - in which there are no constitutional minimums of budgetary application - which makes it more dependent on the political priorities of each elected government. In any case, we believe that the current rules do not prevent states from making a difference in the results of the policy, which, however, does not mean that they are managing to induce them to carry out the responsibilities that have been reserved for them, so that the commitment of these agents remains a challenge to be carried out by the respective arrangements.
Keywords: I38; H77; 330; federalism; state governments; social policies; federative coordination; intergovernmental relations